PEMANFAATAN LIMBAH KACA SEBAGAI SUBSTITUSI SEBAGIAN AGREGAT HALUS BAHAN MATERIAL PEMBUATAN BETON - Rosiyani, Tissa Rahayu; Triyani, Anis; Sintia, Sela; Yudaningrum, Farida (Jurnal Teknik Sipil Giratory UPGRIS, 2025)
Concrete technology has increased in recent decades followed by various studies to improve concrete performance in the construction world. The research conducted is to improve the performance of building materials by considering the selection of concrete forming materials to the substitution of other materials such as replacing an aggregate with waste materials. Therefore and by considering the existence of large amounts of glass waste, it is possible to be used as an alternative solution to environmental problems around us, especially fine aggregates. The study used glass substitution as a partial replacement for fine aggregates in concrete materials. The glass variations used were 0%, 7.5%, 10%, and 12.5%. Data analysis used regression and classical assumption tests with the SPSS program with the help of SPSS 20 for Windows software. The variables used in this study were the independent variable (glass waste) and the dependent variable (compressive strength and flexural strength)